Magnetothermopower and magnetoresistance of single Co-Ni/Cu multilayered nanowires - Boehnert, Tim; Niemann, Anna Corinna; Michel, Ann-Kathrin; Baessler, Svenja; Gooth, Johannes; Toth, Bence G.; Neurohr, Katalin; Peter, Laszlo; Bakonyi, Imre; Vega, Victor; Prida, Victor M.; Nielsch, Kornelius (Physical Review B - Condensed Matter and Materials Physics, 2014)
The magnetothermopower and the magnetoresistance of single Co-Ni/Cu multilayered nanowires with various thicknesses of the Cu spacer are investigated. Both kinds of measurement are performed as a function of temperature (50-325 K) and under applied magnetic fields perpendicular to the nanowire axis, with magnitudes up to -15% at room temperature. A linear relation between thermopower S and electrical conductivity σ of the nanowires is found, with the magnetic field as an implicit variable. Combining the linear behavior of the S vs σ relation and the Mott formula, the energy derivative of the resistivity is determined. In order to extract the true nanowire materials parameters from the measured thermopower, a simple model based on the Mott formula is employed to distinguish the individual thermopower contributions of the sample. By assuming that the nondiffusive thermopower contributions of the nanowire can be neglected, it is found that the magnetic-field-induced changes of thermopower and resistivity are equivalent. The emphasis in the present paper is on the comparison of the magnetoresistance and magnetothermopower results and it is found that the same correlation is valid between the two sets of data for all samples, irrespective of the relative importance of the giant magnetoresistance or anisotropic magnetoresistance contributions in the various individual nanowires.
CRIS-Team Scopus Importer:2023-03-20